Reduce Blood Pressure Values Of Hypertension Patients Using Slow Deep Breathing - Wisuda, Aris Citra; Sasmita Saputra, Muhamad Andika; Suraya, Citra (Yayasan Rumah Ilmu Professor, 2022)
This study aimed to determine the effect of slow deep breathing techniques onblood pressure values in hypertensive patients. This research is a PreExperimental Design with One Group Pretest-Posttest. The sampling technique used is non-probability sampling, purposive sampling with a research sample of22 respondents. Univariate results obtained an average respondent of 60 years, with the majority gender 21 respondents (95.4%). Bivariate results showed that the p-value of the statistical test using the Wilcoxon test was known that the p-value was 0.000 (<0.05). In conclusion, slow deep breathing techniques affect blood pressure values in hypertensive patients at Puskesmas 23 Ilir Palembang in 2022